Pelatihan Diversifikasi Olahan Bawang Merah Menjadi Produk Bernilai Ekonomis Tinggi - Dwi Puji Astuti; Kardiyem Kardiyem; Wulan Suci Rachmadani; Abdul Khafidz (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service program is to help optimize the potential of local resources in the form of shallots available in Genengadal Village, Grobogan to be processed as various shallot products with high selling value. The methodology carried out consists of several stages, namely: (1) Holding a meeting with representatives of the rahayu farmer group to hold training and socialization (2) Focus Group Discussion (FGD) discussing in detail the activity plan while dividing tasks for members of the rahayu farmer group, (3) Conducting training on making processed shallots, namely fried onions and pastries from shallots,Â  (4) Assisting online marketing strategies, and (5) Monitoring and evaluating. Based on the results of the training carried out, the potential of shallots, which was originally not optimally utilized by farmers, has now been able to optimize its usefulness into a product with high economic value. The processed shallots that have been produced are fried onions and pastries. In addition, the products that have been produced are packaged and labeled with attractive packaging that has economic value.